Standard versus minimally invasive transforaminal lumbar interbody fusion: A prospective randomized study. (November 2017) - Tender, Gabriel; Serban, Daniel; DiGiorgio, Anthony
Abstract : Introduction: Symptomatic spondylolisthesis patients may benefit from surgical decompression and stabilization. The standard (S) technique is a transforaminal lumbar interbody fusion (TLIF). Newer, minimally invasive (MI) techniques seem to provide similar results with less morbidity. However, prospective studies comparing S versus MI TLIF are rare. Case description: Patients with at least 6 months of symptoms and image-confirmed low-grade spondylolisthesis (grade 1 or 2) were enrolled, at a single academic institution, between 2011 and 2015. The patients were randomized to either S or MI TLIF. Iliac crest graft, polyether ether ketone (PEEK) interbody cages, and pedicle screw-rod constructs were used in both groups. The primary outcome measure was the Oswestry Disability Index (ODI) improvement at 1 year. Secondary outcome measures included length of operation, estimated blood loss, length of hospitalization, and fusion rates at 1 year. Complications were also recorded. Results and Conclusions: Forty patients were enrolled in each group. There was no crossover between groups. The age was 50.12+/-11.09 years in the S TLIF group and 51.3+/-9.36 years in the MI TLIF group. There were 23 and 24 females in the S and MI TLIF group, respectively. The mean operative time and estimated blood loss in the S versus MI TLIF group were 297+/-101 versus 323 +/-85 minutes and 417+/-211 versus 351+/-198 ml, respectively. There were 4 transfusions in the S TLIF and 3 transfusions in the MI TLIF group. The patients were discharged after surgery at 4.12+/-0.88 days for the S TLIF group and 1.92+/-0.52 days for the MI TLIF group. The ODI improved from 37+/-6 to 11+/-6 in the S TLIF group (ODI difference: 26+/-7) and from 38+/-7 to 11+/-6 in the MI TLIF group (ODI difference: 26+/-8). The fusion was considered solid (Grade I) in 36 (90%) and partial (Grade II) in 4 (10%) patients at 1 year. There were no reoperations for pseudarthrosis or any other postoperative complication. There were 2 superficial wound infections in the standard TLIF group, which resolved with oral antibiotic treatment alone. Take home message: In this prospective randomized study, the standard and minimally invasive TLIF in patients with symptomatic spondylolisthesis provided similar clinical and radiological outcomes at 1 year. The patients undergoing MI TLIF had a shorter hospital stay. Both surgical techniques yielded good results at 1 year.